Congenital peritoneopericardial diaphragmatic hernia in an geriatric Persian cat - Archanjo, Anderson Barros; Azevedo, Marcel Arcanjo Silva; Souza, Dyeime Ribeiro; Trivilin, Leonardo Oliveira; Andrade Júnior, Paulo Sérgio Cruz; Amaral, Camila Barbosa; Nunes, Louisiane Carvalho (Medicina Veterinária, 2020)
Peritoneopericardial diaphragmatic hernia (PPDH) is a rare condition that is caused by defective diaphragm and pericardium development. It occurs in dogs and cats and is most prevalent in Weimaraner and Persian breeds. This study presents the first report of a congenital peritoneopericardial diaphragmatic hernia in a geriatric cat in Espírito Santo in Brazil. A 12-year old male Persian cat was referred to the veterinary hospital. Clinical examination revealed hyporexia, cachexia, alopecia, dyspnea, and an adherent and irregularly shaped nodule in the left caudal breast. Cytopathological examination of the abdominal nodulation revealed a mammary carcinoma. Thoracic radiography revealed PPDH. The animal was euthanized. On necropsy, the abdominal cavity revealed a part of the liver inside the diaphragm, and the thoracic view revealed the heart and liver inside the pericardial sac. Histopathological analysis confirmed mammary carcinoma and revealed dermatophytic pseudomycetoma. This is the first report of PPDH, which was incidentally detected, in a geriatric Persian cat that had survived for several years without diagnosis in Espírito Santo, Brazil. From the observations made, we conclude that comprehensive clinical examination, involving imaging, is important in detecting congenital abnormalities such as PPDH.